GAMBARAN KEBIASAAN KONSUMSI SAYUR DAN BUAH PADA REMAJA - Melinda S. Mahful; Salman Salman; Misnati Misnati; Rahma Labatjo; Misrawati Goi (JOURNAL HEALTH AND NUTRITIONS, 2022)
Vegetables and fruits are foods that are very beneficial to the body, especially to support the need for vitamins. This research aims to determine the picture of vegetable and fruit consumption in adolescents. The research method uses a descriptive survey, which is to describe the variables studied. The population is 210 people, the sample is calculated at 10% of the population of 21 people. The research variable is an independent variable, namely vegetable and fruit consumption in adolescents. The results showed that the distribution of research subjects based on the age group was the largest in the age group of 10-14 years, namely 12 people (57.1%)  while the group of subjects based on sex was the most male, namely 12 people (57.1%), the picture of  vegetable  and fruit consumption showed vegetable  consimsion In adolescents with less categories, there were 14 people (66.7%), 7 people (33.3%). Fruit consumption in adolescents with less categories amounted to 13 people (61.9%), quite 8 people (38.1%). The conclusion of this study is that most adolescents have less consumption rates of vegetables and fruits when  compared to the recommended recommendations.Sayur dan buah merupakan bahan pangan yang sangat memberi manfaat bagi tubuh, terutama untuk mendukung kebutuhan akan vitamin. Penetian ini bertujuan untuk mengetahui gambaran konsumsi sayuran dan buah pada remaja. Metode penelitian menggunakan survey deskriptif yaitu untuk menggambarkan variabel yang diteliti. Populasi sebanyak 210 orang, sampel dihitung sejumlah 10% dari populasi yaitu 21 orang. Variabel penelitian merupakan variabel mandiri yaitu konsumsi sayur dan buah pada remaja. Hasil penelitian menunjukkan distribusi subjek penelitian berdasarkan kelompok umurr paling besar pada kelompok umur 10 – 14 tahun yakni sebanyak 12 orang (57,1%) sementara kelompok subjek berdasarkan jenis kelamin paling banyak laki – laki yakni 12 orang (57,1%), gambaran konsumsi sayur dan buah menunjukkan konsimsi sayur pada remaja dengan kategori kurang berjumlah 14 orang (66,7%), cukup berjumlah 7 orang (33,3%). Konsumsi buah pada remaja dengan kategori kurang  berjumlah 13 orang (61,9%), cukup  berjumlah 8 orang (38,1%). Kesimpulan penelitian ini adalah sebagian besar remaja memiliki tingkat konsumsi sayur dan buah termasuk kategori kurang jika dibandingkan dengan rekomendasi yang dianjurkan.